Bootschaften : Ein Materialienbuch. - Diederichs, Joachim (Wilhelmshaven : Kunsthalle Wilhelmshaven, 1988)
Dietzler, Georg ; Ulrichs, Timm ; Möckel, Ulrich ; Nils-Udo ; Brodwolf, Jürgen ; Len, Ernst ; Sugai, Nobuko ; Virnich, Thomas ; Albrecht, Hans ; Rheinsberg, Raffael ; Jaxy, Constantin ; Visch, Henk ; Katase, Kazuo ; etc.
Ausstellung "Vor-Boote" 08.08.1987 ; Bootschaften : Schiffe und Boote in der zeitgenössischen Kunst, Kunsthalle Wilhelmshaven, 1988
Duits
kunstcatalogus